Antarctica Malaysia's journey to the ice - Nair, M.Govind; Mohamad Nasir Yusoff; Salbiah Said; Saleh Mohd Nor; Azizan Abu Samah; B.A Hamzah; Ewe, Hong Tat; Michael, Clemente Wong Vui Ling ‫‫; Wan Maznah Wan Omar; Hii, Yii Siang; Wayan Suparta; Rosmadi Fauzi; et al. (National Antarctic Research Centre, University of Malaya, 2013)
This coffee table book, 'Antarctica: Malaysia's Journey to the Ice', gives, through text and pictures, an elaborate account of the icy continent, its geology, climate, flora and fauna and the scientific research stations as well as the work of the multinational group of scientists and researchers who focus their efforts there.